2016
DOI: 10.1007/s10384-016-0459-8
|View full text |Cite
|
Sign up to set email alerts
|

Corona sign: manifestation of peripheral corneal epithelial edema as a possible marker of the progression of corneal endothelial dysfunction

Abstract: The slit-lamp microscopic findings of the corona-like epithelial edema in the peripheral cornea are associated with the stage of corneal endothelial function. To support this, the developmental mechanism of the corona sign was demonstrated experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Another interesting study showed that adult endothelial cells were able to migrate in the human eye, supporting that endothelial cell in the donor graft can migrate toward the periphery of the host cornea [27,28]. The transplanted endothelium should compensate for the denuded area by migrating to the peripheral area (Fig 4) [28,29]. Thus, the decrease in ECD after DMEK could be attributed to the distribution of endothelial cells to the peripheral area, especially in BK eyes, although other factors could also play a role.…”
Section: Plos Onementioning
confidence: 87%
“…Another interesting study showed that adult endothelial cells were able to migrate in the human eye, supporting that endothelial cell in the donor graft can migrate toward the periphery of the host cornea [27,28]. The transplanted endothelium should compensate for the denuded area by migrating to the peripheral area (Fig 4) [28,29]. Thus, the decrease in ECD after DMEK could be attributed to the distribution of endothelial cells to the peripheral area, especially in BK eyes, although other factors could also play a role.…”
Section: Plos Onementioning
confidence: 87%
“…This postoperative optical abnormality might be a limitation in some eyes after DMEK. Inoue et al reported a swirling pattern of horizontal water migration in the cornea in human and rabbit eyes,[ 24 , 25 ] which is identical to the anatomic pattern of the corneal nerve. Because DMEK replaces dysfunctional endothelium, key factors in need of investigation include an uneven distribution of endothelial cell density.…”
Section: Discussionmentioning
confidence: 97%